2011
DOI: 10.1016/j.ijid.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of clinical symptoms in dengue-infected persons and its association with immunological disorders

Abstract: Clinical sequelae after recovery from an acute dengue virus infection are common in the 2 years following infection. The results obtained in this study suggest that persistent symptoms are associated with alterations in some immunological parameters and FcγRIIa gene polymorphism. This could suggest an autoimmune-based disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 25 publications
(31 reference statements)
2
78
1
4
Order By: Relevance
“…15 Nevertheless, host immunological factors may be important, as others have shown that genotypic differences in the immune receptor FcγRII correlate with long-term persistence of symptoms after DENV infection. 13 Although only a handful of prior reports describe and enumerate symptom persistence after the acute febrile period with dengue fever, this phenomenon has been described for other arboviral infections. For example, the alphaviruses CHIKV, MAYV, and Ross River virus may cause joint pain that lasts weeks to years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Nevertheless, host immunological factors may be important, as others have shown that genotypic differences in the immune receptor FcγRII correlate with long-term persistence of symptoms after DENV infection. 13 Although only a handful of prior reports describe and enumerate symptom persistence after the acute febrile period with dengue fever, this phenomenon has been described for other arboviral infections. For example, the alphaviruses CHIKV, MAYV, and Ross River virus may cause joint pain that lasts weeks to years.…”
Section: Discussionmentioning
confidence: 99%
“…22 Looking at time periods beyond the acute visit, a study from Singapore evaluating fatigue after 2 months and a study from Cuba examining multiple symptoms after 2 years both noted higher levels of persistent symptoms in females. 10,13 Females have also been noted to have a worse prognosis or slower recovery after West Nile virus (WNV), CHIKV, and tick-borne encephalitis virus (TBEV) infections. [23][24][25] Consistent with our findings, others have shown that older age impacts many different outcomes of DENV infection, both in the acute presentation and subsequent outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Su etiología aún no se ha descrito con precisión, de la fase aguda, entre los cuales predominó el cansancio físico (65,6 %), la cefalea (37,5 %), el insomnio (31,3 %), el mareo, el cansancio mental (25 %) y el dolor muscular (18,8 %). Estos hallazgos coinciden con las observaciones registradas en otros estudios (16,(28)(29)(30). Al evaluar la presencia de fatiga física y mental después de la infección aguda por dengue, se evidenció que esta se mantuvo en 34,4 % de los pacientes durante su convalecencia, con síntomas como el Convalecencia de la infección del dengue Figura 2.…”
Section: Discussionunclassified
“…Naturally, these health problems (and avoiding them via vaccination) can impact educational attainment, adult earnings, and social functioning (31)(32)(33)(34)(35). Thus, outcome-related productivity gains are benefits that follow on from improved health due to vaccination.…”
Section: Broader Perspective On the Value Of Vaccinationmentioning
confidence: 99%